Eastern rockhopper penguins Eudyptes filholi as biological samplers of juvenile and sub-adult cephalopods around Campbell Island, New Zealand - Xavier, José C. (2020)
Early life-history stages of cephalopods are known to play an important role as prey in food webs of the Southern Ocean, but little information is available about their biology and availability to predators. Top predators, such as penguins, are known to feed regularly on coastal juvenile/sub-adult cephalopods. Using eastern rockhopper penguins Eudyptes filholi as coastal biological samplers, we examined in detail the cephalopod component of their diet in Campbell Island (New Zealand) during two consecutive breeding seasons in order to evaluate (1) the relative importance of cephalopods (by frequency of occurrence, by number and by mass) to the diet of both adult and chick penguins, (2) the habitat and trophic levels of the cephalopods in the region and (3) the status of the juvenile/sub-adult cephalopod community in the waters around Campbell Island. Our results show that eastern rockhopper penguins feed on eight species of juvenile and sub-adult cephalopods, with Onykia ingens, Martialia hyadesi and Octopus campbelli being the most important species by frequency of occurrence, number and mass. Differences between the diets of adult and chick penguins and between breeding seasons were found. Habitat (δ13C) and trophic level (δ15N) information also showed that all cephalopod species (and all studied stages) occupy similar habitat on the Campbell shelf, with M. hyadesi showing lower δ15N values than O. ingens and O. campbelli. This study indicates that eastern rockhopper penguins can be valuable biological samplers of local juvenile/sub-adult cephalopods (including poorly known cephalopod species) around Campbell Island when breeding, that these cephalopods were likely to be caught naturally (not from fisheries), providing relevant information for the conservation of these penguins.